Approach to pactamycin analogues using rhodium(ii)-catalyzed alkene aziridination and C(sp3)–H amination reactions. Issue 6 (21st December 2017) - Rodrigues, Romain; Lazib, Yanis; Maury, Julien; Neuville, Luc; Leboeuf, David; Dauban, Philippe; Darses, Benjamin
Abstract : Application of dirhodium(ii )-catalyzed nitrene transfers allows for the preparation of a platform bearing the triamino moiety present in pactamycin. Abstract : Dirhodium(ii )-catalyzed nitrene transfers have been used to prepare a novel synthetic platform bearing the triamino moiety present in pactamycin, jogyamycin and cranomycin. Catalytic intramolecular C(sp 3 )–H amination and alkene aziridination reactions, the latter followed by a nucleophilic aziridine ring opening, are the key steps of this strategy.